Sustainable Practices of Smart Mobility Service (SMS): A Case Study of Public Transportation System in Kuala Lumpur, Malaysia - Thillai Raja Pertheban; Sarah Basel Oqbah (International Journal of Supply Chain Management, 2022)
The public transportation system contributing immensely to national economic progress. Regardless of various obstacles, the public transportation system has achieved growth. This study aimed to examine the influences of sustainable practices of Smart Mobility Service (SMS) of public transportation system in Kuala Lumpur, Malaysia. The key objective this study to justify the relationship between sustainable practices such as Smart Governance (SG), Smart Infrastructure (SI), Smart Technology (ST), Smart Citizen (SC) are proposed to justify is there any significant relationships with Smart Mobility Services (SMS) in public transportation system in Kuala Lumpur. This research believes that the basis to determine the Smart Mobility Services (SMS) in public transportation system. Limitations of the study are discussed and directions for future research are suggested.